Method for determining the expected efficiency of water production - Rak, Janusz; Stec, Aleksandra (Instal, 2024)
The systematics of threats to collective water supply systems requires multidirectional divisions. Technical risk is an increasing function of negative impact. Technical safety is a decreasing function of possible harm. Both of these measures can be identified with the risk of negative impact and the risk of harm. As a result of the solutions introduced in this work, two new indicators for assessing risk to the security of collective water supply were proposed: the system resilience index (Ir) and expected water production efficiency index (EWPEI). The paper gives examples of applications of the method for determining EWPEI.